Addition of high-dose cytarabine to immunochemotherapy before autologous stem-cell transplantation in patients aged 65 years or younger with mantle cell lymphoma (MCL Younger): a randomised, open-label, phase 3 trial of the European Mantle Cell Lymphoma Network. Issue 10044 (6th August 2016) - Hermine, Olivier; Hoster, Eva; Walewski, Jan; Bosly, André; Stilgenbauer, Stephan; Thieblemont, Catherine; Szymczyk, Michal; Bouabdallah, Reda; Kneba, Michael; Hallek, Michael; Salles, Gilles; Feugier, Pierre; et al.
Summary: Background: Mantle cell lymphoma is characterised by a poor long-term prognosis. The European Mantle Cell Lymphoma Network aimed to investigate whether the introduction of high-dose cytarabine to immunochemotherapy before autologous stem-cell transplantation (ASCT) improves outcome. Methods: This randomised, open-label, parallel-group, phase 3 trial was done in 128 haemato-oncological hospital departments or private practices in Germany, France, Belgium, and Poland. Patients aged 65 years or younger with untreated stage II–IV mantle cell lymphoma were centrally randomised (1:1), with computer-assisted random block selection, to receive either six courses of R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) followed by myeloablative radiochemotherapy and ASCT (control group), or six courses of alternating R-CHOP or R-DHAP (rituximab plus dexamethasone, high-dose cytarabine, and cisplatin) followed by a high-dose cytarabine-containing conditioning regimen and ASCT (cytarabine group). Patients were stratified by study group and international prognostic index. The primary outcome was time to treatment failure from randomisation to stable disease after at least four induction cycles, progression, or death from any cause. Patients with stage II–IV mantle cell lymphoma were included in the primary analysis if treatment was started according to randomisation. For safety analyses, patients were assessed according to the treatment actually started. This study is registered withClinicalTrials.gov, numberNCT00209222 . Findings: Of 497 patients (median age 55 years [IQR 49–60]) randomised from July 20, 2004, to March 18, 2010, 234 of 249 in the control group and 232 of 248 in the cytarabine group were included in the primary analysis. After a median follow-up of 6·1 years (95% CI 5·4–6·4), time to treatment failure was significantly longer in the cytarabine group (median 9·1 years [95% CI 6·3–not reached], 5 year rate 65% [95% CI 57–71]) than in the control group (3·9 years [3·2–4·4], 40% [33–46]; hazard ratio 0·56; p=0·038). During induction immunochemotherapy, patients who received high-dose cytarabine had increased grade 3 or 4 haematological toxicity (haemoglobin 71 [29%] of 241m vs 19 [8%] of 227 controls; platelets 176 [73%] of 240 vs 21 [9%] of 225), grade 3 or 4 febrile neutropenia (39 [17%] of 230 vs 19 [8%] of 224), and grade 1 or 2 renal toxicity (creatinine 102 [43%] of 236 vs 22 [10%] of 224). The number of ASCT-related deaths was similar (eight [3·4%]) in both groups. Interpretation: Immunochemotherapy containing high-dose cytarabine followed by ASCT should be considered standard of care in patients aged 65 years or younger with mantle cell lymphoma. Funding: European Commission, Lymphoma Research Foundation, and Roche.